Penegakan Hukum Pada Era Globalisasi Ekonomi Dalam Perspektif Keadilan Pancasila - Putra, Tegar Harbriyana (Universitas Muhammadiyah Metro, 2025)
Globalization is a social and cultural process that begins with the interaction of one nation with another. Globalization can be defined as a condition of interdependence within an international network encompassing transportation, distribution, communication, and economics that transcends national territorial boundaries. Pancasila is the source of all sources of law. Therefore, all legal products, whether laws or other legal products, must be in accordance with the values contained in Pancasila. The problem formulation that will be used as a framework in writing this research is as follows: How does economic globalization influence the concept of law enforcement in Indonesia? How is law enforcement viewed from the perspective of Pancasila justice? This research uses a normative juridical approach and is qualitative in nature with a descriptive method. The influence of economic globalization on national law enforcement in Indonesia is a complex and multidimensional phenomenon. The influence of globalization has been the main driver of change in the legal system and law enforcement in Indonesia, affecting regulations, policies, and legal practices in various fields. The rapid development and progress in various fields, such as the flow of trade, investment, and increasingly open information, have created new challenges in maintaining legal sovereignty and national interests. Law (in the context of law enforcement) and justice have Law (in the context of law enforcement) and justice play an important role in achieving the goals of Pancasila. With Pancasila in the legal system, we can build a solid foundation for achieving social justice and national progress. Law enforcement in Indonesia must reflect the values contained in Pancasila, which are then implemented in social, national, and state life, both at the national and international levels